2013
DOI: 10.1248/cpb.c13-00145
|View full text |Cite
|
Sign up to set email alerts
|

Methyl 5-Chloro-4,5-didehydrojasmonate (J7) Inhibits Macrophage-Derived Chemokine Production <i>via</i> Down-Regulation of the Signal Transducers and Activators of Transcription 1 Pathway in HaCaT Human Keratinocytes

Abstract: Key words jasmonate; signal transducers and activators of transcription 1; HaCaT keratinocyte Jasmonic acid and its methyl ester, methyl jasmonate, are fatty acid-derived cyclopentanones that are synthesized from linolenic acid residing in the chloroplast membrane. These lipid-based stress hormones occur throughout the plant kingdom and play major roles in the defense of plants against insects and disease. Many reports suggest that jasmonates can also suppress the proliferation of various cancer cells, leading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…In our study, treatment with TNF-α and IFN-γ markedly increased the production and expression of the chemokines TARC, MDC, RANTES, and IL-8 in HaCaT cells; this finding is consistent with that of previous studies (Han et al 2011;Kang et al 2013;Kwon et al 2012). By contrast, treatment with JYGCT water extract significantly reduced TARC, MDC, RANTES, and IL-8 secretion and expression at the mRNA level in TNF-α and IFN-γ -stimulated HaCaT cells (Figs.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, treatment with TNF-α and IFN-γ markedly increased the production and expression of the chemokines TARC, MDC, RANTES, and IL-8 in HaCaT cells; this finding is consistent with that of previous studies (Han et al 2011;Kang et al 2013;Kwon et al 2012). By contrast, treatment with JYGCT water extract significantly reduced TARC, MDC, RANTES, and IL-8 secretion and expression at the mRNA level in TNF-α and IFN-γ -stimulated HaCaT cells (Figs.…”
Section: Discussionsupporting
confidence: 93%
“…Studies have shown that STAT and/or NF-κB activation are mediated by TNF-α and/ or IFN-γ in keratinocytes. [9][10][11][12] Because the promoters of MDC, and RANTES contain STAT-and NF-κB-binding sites, 34,35) it is possible that chemokine production can be regulated via activation of the STAT1 and NF-κB pathways. We found that TNF-α and IFN-γ treatment increased the level of phospho-STAT1 in HaCaT cells, whereas treatment with GJBRH extract markedly reduced this phosphorylation of STAT1 (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Among the members of the STAT family proteins, STAT1 plays a critical role in the regulation of primary inflammatory responses. 7,8) In keratinocytes, STAT1 is a pivotal regulator of the IFN-γ and/or TNF-α-stimulated immune responses [9][10][11][12] and eventually stimulate the production of chemokines, including TARC, MDC, and RANTES. 13,14) Thus, STAT1 is considered an important molecule for studying inflammatory disorders of skin, including atopic dermatitis.…”
mentioning
confidence: 99%
“…In this sense, MeJA and its analogues have the potential to inhibit TNF production in murine macrophage and HCAT keratinocyte cells . To date, in clinical practice, only antibody therapy has been found to be an efficient method of neutralizing the effects of TNF in patients with chronic inflammatory conditions such as IBDs …”
Section: Meja: a Potential Phytohormone For Anti‐tnf Therapy In The Tmentioning
confidence: 99%
“…[70] In this sense, MeJA and its analogues have the potential to inhibit TNF production in murine macrophage [40] and HCAT keratinocyte cells. [71] To date, in clinical practice, only antibody therapy has been found to be an efficient method of neutralizing the effects of TNF in patients with chronic inflammatory conditions such as IBDs. [72] The first hypothesis is based on the possible therapeutic potential of MeJA in the modulation of IBDs, suggesting an anti-regulatory mechanism, based on the reduction of the expression of TNF tissue levels, minimizing apoptosis in the intestinal crypts with a direct effect on the apoptotic extrinsic pathway.…”
Section: Intestinal Apoptosismentioning
confidence: 99%